Lethality Test of Some Varieties of Sea Cucumber Extract Against Artemia Salina, as Natural Food Additive in Meat-Based Functional Food - Djoko Kisworo; Sukirno; Bulkaini (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2021)
Abstract Cancer is the main cause of death in the world with the number of sufferers in 2008 as many as 12.7 million with a death rate of 7.6 million people. In Indonesia, it is estimated that there are more than 1 million cancer patients in 2010. One of the ways to prevent cancer is primary prevention by adjusting the pattern and type of food consumed. Functional food introduced by bioactive components from sea cucumbers is an alternative for cancer prevention. The specific objective of this research was to produce meat-based functional foods containing anti-cancer compounds derived from sea cucumbers that can prevent cancer. The preliminary tests conducted were the sea cucumber extract lethality test against Artemia salina, namely the Brine Shrimp Lethality Test (BSLT), and the total bacteria of beef meatballs. The results of the observation of the lathality of sea cucumber extract against Artemia salina and total bacteria of the meatball showed that the sea cucumber extract had high lathality against Artemia salina and was able to reduce the total bacteria in meatballs during storage period. The lathality of sea cucumber extract was strongly influenced or stimulated by heating treatment. Based on the BSLT test, of the five types of sea cucumbers, two of them (Holothuria similis and Pearsonothuria graeffei) have high lathality. Sea cucumber extract was also able to inhibit both bacterial and fungal growth in meatballs during storage at room temperature. Keywords: Beef Meatballs, Total Bacteria, Sea Cucumber, BSLT.